Space travelers - Simon, Seymour (San Francisco : SeaStar Books, 2003)
Traces the history of space travel, looking at some of the achievements that have been made since the beginning of manned flight, and imagining what the future might hold for traveling and living in outer space.
"Grades 2-4"--Cover.
5.0
K-3
Keywords: Astronautics -- History -- Juvenile literature; Astronautics -- History; Astronautics -- History